A molecular determinant of phosphoinositide affinity in mammalian TRPV channels - Velisetty, Phanindra (Sci Rep, 2016)
Phosphatidylinositol 4,5-bisphosphate [PI(4,5)P(2)] is an important cofactor for ion channels. Affinity for this lipid is a major determinant of channel inhibition by depletion of PI(4,5)P(2) upon phospholipase C (PLC) activation. Little is known about what determines PI(4,5)P(2) affinity in mammalian ion channels. Here we report that two members of the Transient Receptor Potential Vanilloid (TRPV) ion channel family, TRPV5 and TRPV6 lack a positively charged residue in the TM4-TM5 loop that was shown to interact with PI(4,5)P(2) in TRPV1, which shows high affinity for this lipid. When this positively charged residue was introduced to either TRPV6 or TRPV5, they displayed markedly higher affinities for PI(4,5)P(2), and were largely resistant to inhibition by PI(4,5)P(2) depletion. Furthermore, Ca(2+)-induced inactivation of TRPV6 was essentially eliminated in the G488R mutant, showing the importance of PLC-mediated PI(4,5)P(2) depletion in this process. Computational modeling shows that the introduced positive charge interacts with PI(4,5)P(2) in TRPV6.